Left atrial appendage occlusion with Amplatzer Cardio Plug is an acceptable therapeutic option for prevention of stroke recurrence in patients with non-valvular atrial fibrillation and contraindication or failure of oral anticoagulation with acenocumarol - Maximiliano A. Hawkes; Lucía Pertierra; Federico Rodriguez-Lucci; Virginia A. Pujol-Lereis; Sebastián F. Ameriso (Arquivos de Neuro-Psiquiatria)
ABSTRACT Left atrial appendage occlusion (LAAO) appears as a therapeutic option for some atrial fibrillation patients not suitable for oral anticoagulation because an increased hemorrhagic risk or recurrent ischemic events despite anticoagulant treatment. Methods Report of consecutive atrial fibrillation patients treated with LAAO with Amplatzer Cardio Plug because contraindication or failure of oral anticoagulation with acenocumarol. CHA2DS2VASC, HAS-BLED, NIHSS, mRS, procedural complications and outcome were assessed. Seven patients (73 ± 6 year-old) were treated after intracerebral (n = 5) and gastrointestinal (n = 1) hemorrhages or ischemic stroke recurrence while on acenocumarol (n = 1). Results Mean follow up was 18 months. Baseline CHA2DS2Vasc y HAS-BLED scores were 5.6 ± 0.7 and 4.1 ± 0.3 respectively. There were no strokes or deaths. There was only one non-serious adverse event. Conclusion LAAO with ACP appears as a feasible therapeutic option for stroke prevention in patients with atrial fibrillation and failure or contraindication to acenocumarol.